Orphans and Families of Martyrs of Terrorism Expert System-OFMTES - اسراء مؤيد (College of Education for Women, 2019)
The increasing number of orphans and their organizations and institutes in our community makes it increasingly important to design and develop an expert system that supports decisions concerning orphans and their families. This system can be used by any orphans organization to facilitate its work. The proposed work is designed to manage the Orphans and Families of Martyrs of Terrorism Expert System (OFMTES) by registry all information about all orphans to display mostly orphan deserves bill, data is entered for each orphan, and with each entry a counter is increased according to this input information; the output result represents the score for that orphan. Different orphans have different scores. Coloring is used to know the degree of orphans merit; that is, when background color of that text is red this means that the orphan does not deserve bill, when the color is yellow this means that the orphan deserves bill but in little ratio, when the color is blue this means that the orphan deserves bill but in more ratio from blue, and when the color is green this orphan is mostly deserves bill. The program was implemented using Microsoft office access 2003 and visual basic programming language, and can be executed using Pentium two or more computer. Keywords: Expert system, knowledge engineering, decision support system, Knowledge Representation, Information Technology and Artificial Intelligence.